Application and efficacy analysis of rituximab in the treatment of childhood primary nephrotic syndrome in Ningxia - Wu Yang; Xiao-e Wang; Jia-le Gu; Li-juan Ma; Bai-ge Su; Hui-jie Xiao; Yong Yao; Hong-wen Zhang (Editorial Department of Journal of Clinical Nephrology, 2024)
ObjectiveRituximab (RTX) has been widely used for primary nephrotic syndrome (PNS) in children of frequent relapse or hormonal dependence. The authors applied RTX for childhood PNS in Ningxia for the first time and examined its efficacy.MethodsFrom January 1, 2020 to December 31, 2022, 7 PNS children received 3-year RTX dosing with parental consents after poor outcomes of glucocorticoids alone or glucocorticoids plus other immunosuppressants. There were 4 boys and 3 girls with an age range of (4.4-13.0) year. Urinary routine, urinary protein quantification and infection status were regularly monitored for evaluating the treatment effect, safety and expenses.ResultsAll of them were hormonal sensitive with a frequent recurrence. Two to 5 doses of RTX per child were offered over a follow-up period of (9-35) month. Urinary protein stayed long-term negative. There was only 1 relapsing case. Five cases discontinued glucocorticoids and immunosuppressants. No severe infection occurred. The average monthly expense per child after RTX dosing was significantly lower than that before dosing.ConclusionRTX is a safe, economic and effective treatment for PNS children. Early application of RTX may taper glucocorticoids and/or immunosuppressants and minimize adverse reactions.